Underground Economy (UGE) Terhadap Kehilangan Potensi Pajak di Indonesia - Susilo, Yuvensius Sri; Kumowal, Fabritio Paulus; Herawan, Jonathan Ersten (Journal of Business and Economics Research (JBE), 2024)
This study aims to determine the amount of loss of tax revenues experienced by Indonesia due to underground economic activities. Using secondary time series data from Q-1 2010 to Q-4 2022 with an analytical method that uses a monetary approach, namely the regression equation for the demand for currency with the Error Correction Models (ECM) model. In the classical assumption test conducted, the data in this study were normally distributed in the normality test, there was no multicollinearity, no heteroscedasticity, and no autocorrelation. The hypothesis of this study is that there is an allegation that the variables GDP, interest rates, financial innovation, bank developments, and tax burdens affect the demand for currency in society. The results of this study are that the GDP, interest rate, and tax burden variables have a significant effect on the demand for currency with an average assessment of the underground economy (UGE) activity variable reaching IDR 79,936 billion and the value of tax losses experienced by the state amounting to IDR 16,776 billion every year.